Surrogate motherhood: Rationale for her penalty, 2012 Tacna Region - Montoya Vargas, Ema Dolores (2013)
Objetive: Know the results of an investigation into the  criminal sanction of surrogate motherhood to be human  commerce, in Tacna Region, 2012.  Method: Non-experimental design being cross-sectional  and basic type. Among the variables studied are: surrogate  motherhood and punishment; between indicators are  punishable conduct, criminal policy, the appropriate  sanction and civil damages.  We worked with a total population consisting of judicial  officers in the exercise, women and judges of the Superior  Court of Tacna. The sample was calculated at 351, 381, 7  respectively.  For data collection, were developed two questionnaires  aimed at older women and justice operators of Tacna - 11  items each and a structured interview conducted by the  Judges of the Superior Court of Justice of Tacna - 7  questions - according to the variables with their respective  indicators. Result: With surrogate motherhood the fundamental  rights are damaged of mothers, but mostly the unborn,  would be necessary the typing and subsequent  punishment of the surrogate motherhood.  Conclusion: Surrogate motherhood constitutes human  trade, must be sanctioned held criminally. Based in the  axiological